KAPITALISME SEBAGAI SEBUAH RISIKO DALAM PEMBANGUNAN IKN - Didik Bagus Setiawan; Daryono Daryono; Eka Ratna Amelia; Eduwin Eduwin (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
This research explores the impact of relocating the capital city (IKN) in Indonesia. Government regulations provide facilities for investors, while global risks, according to Ulrich Beck's concept, continue to evolve in the context of modern society. The history of capital relocation is traced from colonial times to the present, with a focus on security reasons. This study employs a literature review method to gather and analyze data from various sources such as articles, books, and journals. The results of this analysis are then used as a basis for a concrete and exploratory discussion of the issues under investigation. The study's findings indicate both pros and cons regarding the relocation of the capital. Economic evaluations suggest that the impact on economic growth may not be significant. In conclusion, this research highlights that the relocation of the capital is a complex issue, and a thorough evaluation is necessary to understand its impact on Indonesian society and the economy.